Estimating earnings assimilation of immigrants to Germany: Evidence from a double cohort model - Sarah Okoampah (RWI - Leibniz-Institut für Wirtschaftsforschung, 2016)
Following the seminal work of Chiswick (1978), many studies have examined the extent to which earnings of immigrants vary over the settlement process. While these studies usually find that the initial earnings gap between native and immigrant workers in traditional immigration countries disappears as the duration of residence in the host country increases, empirical evidence mostly suggests that immigrants to Germany experience persistent earnings disadvantages and, if at all, only a moderate earnings assimilation process for some immigrant groups. However, due to variations in the economic performance of different immigration cohorts, estimates derived from crosssectional models may be biased (Borjas, 1985). Against this background, this paper employs a double cohort model to revisit the existing evidence on earnings assimilation processes of immigrants to Germany. In line with this literature, no evidence for a robust assimilation process for immigrants is found, even after accounting for potential cohort effects. – – Der richtungsweisenden Studie von Chiswick (1978) folgend haben zahlreiche Studien das Ausmaß untersucht, mit welchem die Löhne von Einwanderern während des Ansiedlungsprozesses variieren. Während diese Studien für traditionelle Einwanderungsländer typischerweise feststellen, dass der anfängliche Lohnnachteil von Einwanderern gegenüber Einheimischen mit zunehmender Aufenthaltsdauer im Gastland verschwindet, deutet die Evidenz für Deutschland hauptsächlich auf persistente Lohnnachteile für Einwanderer hin und impliziert, wenn überhaupt, nur einen moderaten Einkommensassimilationsprozess für einige Einwanderergruppen. Aufgrund von Unterschieden im ökonomischen Erfolg verschiedener Einwanderungskohorten könnten Ergebnisse, die auf Querschnittsmodellen beruhen, jedoch verzerrt sein (Borjas, 1985). Vor diesem Hintergrund schätzt die vorliegende Studie ein Doppelkohortenmodell zur Überprüfung der bestehenden Evidenz zu Einkommensassimilationsprozessen von Einwanderern nach Deutschland. Die Literatur bestätigend, kann auch nach Kontrolle für potentielle Kohorteneffekte kein robuster Einkommensassimilationsprozess nachgewiesen werden.
Keywords: F22; F15; J31; 330; earnings assimilation; cohort effects; international migration